Clinical Decision Support Tool for Elevated Pediatric Blood Pressures. (June 2022) - Meisner, Joshua K.; Yu, Sunkyung; Lowery, Ray; Liang, Wen; Schumacher, Kurt R.; Burrows, Heather L.
Under-diagnosis of pediatric hypertension remains pervasive due to difficulty recognizing elevated systolic blood pressures (SBPs). We performed a retrospective review comparing recognition of and response to elevated SBPs ≥95th percentile before and after development of a clinical decision support tool (CDST) in an academic pediatric system. Of 44, 351 encounters, 477 had elevated SBPs with documented recognition of an elevated SBP in 17.9% of encounters pre-CDST that increased to 33.7% post-CDST ( P = .001). Post-CDST, 75.5% of elevated SBPs had repeat measurement, with 90.8% of initially elevated SBPs normalizing to <95th percentile. If repeat measurement was obtained and SBP remained elevated, documented recognition increased from 14.0 to 83.3% ( P < .0001). These data support using the CDST is associated with increased identification of elevated SBPs in children with greatest improvements associated with repeat SBP measurement. This suggests targeted training and support systems at medical intake would be high yield for increasing recognition of elevated SBP.